Barry S. Schermer: Lessons in Life and Law - Tom K. O'Loughlin II (Washington University Journal of Law & Policy, 2017)
The Article recounts some judicial and life lessons attributed to Judge Barry Schermer. O’Loughlin recounts his initial and subsequent interactions with Judge Schermer in Cape Girardeau, Missouri, and how these moments have shown the Author a bevvy of important things to keep in mind in his practice.
Keywords: Bankruptcy; Judge Schermer; Chapter 11 Bankruptcy